Pertanggungjawaban Pidana terhadap Pelaku Penyebaran Berita Bohong (Hoax) Terkait Informasi Kesehatan di Masa Pandemi Covid-19 - Kadek Rizky Bhaswara Ardiwenatha; Nyoman Gede Sugiartha; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2021)
Hoax news is news that cannot be accounted for by the makers of fake news. Fake news about health information during the pandemic Covid-19 is very dangerous for the public. This study aims to determine the legal arrangements and accountability for the perpetrators of hoax in the midst of the Covid-19 pandemic. The formulation of the problem in this research is how the legal arrangements for the perpetrators of hoax spread in the middle of the Covid-19 pandemic and how criminal responsibility is for the perpetrators of hoax spread in the middle of the covid-19 pandemic. This study uses a normative legal research method using a statutory approach. This study uses a normative legal research method using a statutory approach. The main source of this research is legislation. The results in this study are crimes that can be imposed on the perpetrators of spreading fake news in the midst of the Covid-19 pandemic namely Article 14 paragraph (}),paragraph (2), Article 15 Article 14 paragraph ( 1 ) and Article 45A paragraph ( 1) and (2) .and article 28 of Law No. 11 of 2008 on Information and Electronic Transactions. For the government, the Government should supervise every content on electronic media in Indonesia.